2016
DOI: 10.1080/14763141.2016.1226381
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between foot strike pattern, running speed, and footwear condition in recreational distance runners

Abstract: Compared to competitive runners, recreational runners appear to be more prone to injuries, which have been associated with foot strike patterns. Surprisingly, only few studies had examined the foot strike patterns outside laboratories. Therefore, this study compared the foot strike patterns in recreational runners at outdoor tracks with previously reported data. We also investigated the relationship between foot strike pattern, speed, and footwear in this cohort. Among 434 recreational runners analysed, 89.6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 51 publications
1
29
2
2
Order By: Relevance
“…The present study observed no change in the foot-strike patterns as running speeds increased. Although there is a general understanding that the point of contact shifts from the rear toward the anterior part of the foot as running speed increases (Cheung et al, 2017), this may not be true for speeds below 5 m/s (Breine et al, 2014; Hatala et al, 2013), i.e., within the range adopted in the present study. This contrasting evidence across studies highlights the fact that the relationship between running speed and foot-strike patterns is complex and needs to be examined further, particularly considering long distance running pace.…”
Section: Discussionmentioning
confidence: 70%
“…The present study observed no change in the foot-strike patterns as running speeds increased. Although there is a general understanding that the point of contact shifts from the rear toward the anterior part of the foot as running speed increases (Cheung et al, 2017), this may not be true for speeds below 5 m/s (Breine et al, 2014; Hatala et al, 2013), i.e., within the range adopted in the present study. This contrasting evidence across studies highlights the fact that the relationship between running speed and foot-strike patterns is complex and needs to be examined further, particularly considering long distance running pace.…”
Section: Discussionmentioning
confidence: 70%
“…The strike pattern is another relevant aspect that must be considered on the study of BF running training. Although strike pattern may limit BF effects [8,63], it seems to be also determined by footwear condition [64,65]. Due to its complexity, strike pattern appears as an issue that should be investigated more deeply.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increasing interest in footstrike pattern detection during running, possibly because of its potential relationship with injury [13] and performance [4]. There are three types of footstrike patterns: rearfoot strike (RFS) refers to when the heel lands before the ball of the foot; forefoot strike (FFS) refers to when the ball of the foot lands before the heel; and midfoot strike (MFS) refers to when the ball and heel of the foot land at similar times [5].…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanically, a MFS is the optimal footstrike pattern but past research has indicated that runners find it difficult to self-adjust to a MFS [1]. Regarding running performance, when speed is increased by 1 m/s, the odds of having a FFS or MFS relative to RFS increased by 2.3 and 2.6 times, respectively [9]. Hence, it may be beneficial to provide real time information about footstrike pattern to runners.…”
Section: Introductionmentioning
confidence: 99%